Egalitarian Education: The Practice of Independent Learning at PAUD Sanggar Anak Alam Nitiprayan Kasihan Bantul Yogyakarta - Rohinah, Rohinah; Indriyani, Septi; Aziz, Abdul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
Education at early childhood education (PAUD) Sanggar Anak Alam (SALAM) in Yogyakarta focuses on liberating and holistic development, nurturing students' faith, character, health, knowledge, independence, creativity, and responsibility through a research-based approach centered on nature and individual talents. Unlike traditional schools, SALAM, often called a 'school of life' or 'life laboratory,’ emphasizes experiential learning in a natural setting, aligning education with each student's unique interests and abilities. This study aims to analyze how the concept and practice of independent education are applied at PAUD Sanggar Anak Alam Yogyakarta. Employing a descriptive-qualitative approach, the research investigates how this educational philosophy translates into practice, emphasizing critical thinking, autonomy, and humanization. Through participatory observation, in-depth interviews, and document analysis, the study captures the perspectives of educators, administrators, and other stakeholders. Key findings include the integration of Freire's concepts into pedagogical practices, such as fostering egalitarian educator-student relationships, prioritizing dialogue, and embedding ethics in the curriculum. The study also examines the practical implications of this approach, highlighting the roles of educators as facilitators and the importance of nurturing environmental awareness and critical thinking from an early age. While the study's findings affirm the potential of Freire's model in early childhood settings, its context-specific nature and focus on a single institution necessitate caution in generalizing the results. Consequently, the research underscores the need for further exploration in diverse educational contexts. The study's implications extend to educational policy and practice, advocating a shift towards more participatory, student-centered, and dialogue-driven learning environments. This research contributes to the discourse on global educational reform by demonstrating the transformative power of liberatory education in fostering egalitarian and humanizing educational experiences.